Formulasi Masker Wajah Organik dengan Kunyit: Studi pH, Kadar Air, dan Aktivitas Antioksidan - Suci Nurazmi; Mawardi Mawardi; Desy Kurniawati (MASALIQ, 2025)
This study is motivated by the limited research on the formulation of organic masks using locally sourced natural ingredients such as coffee grounds, rice flour, and turmeric, which hold potential for producing cosmetic preparations with high bioactive efficacy and safety. The objective of this research is to analyze the effect of turmeric addition on the chemical characteristics of organic facial masks made from coffee grounds and rice flour, with a focus on pH level, moisture content, antioxidant activity, and flavonoid content. A quantitative approach was employed through laboratory experiments involving two formulations (with and without turmeric), each tested in triplicate. pH was measured using a digital pH meter; moisture content was determined by the gravimetric method; antioxidant activity was assessed using the DPPH method with a UV-Vis spectrophotometer; and flavonoid content was evaluated qualitatively. The results show that the formulation containing turmeric had a more neutral pH (7.3), lower moisture content (3.11%), higher antioxidant activity (47.50%), and tested positive for flavonoid content. In contrast, the formulation without turmeric had higher moisture content (3.68%) and did not contain flavonoids. The addition of turmeric also influenced drying time, though it remained within an optimal range. The study concludes that turmeric addition significantly enhances the chemical quality and biofunctional activity of the mask, representing an innovative approach to developing herbal cosmetics based on local ingredients.